Supporting innovation and the use of technologies in accountability initiatives: lessons from Making All Voices Count - and Edwards, Duncan; Hudson, Hannah; Anderson, Colin; McGee, Rosemary; Brock, Karen (IDS, 2018)
Making All Voices Count was an international initative that harnessed the power of innovation and new technologies to support effective, accountable governance. Focusing on six countries in Africa and Asia, the programme was implemented by a consortium of implementing partners, and used funding from four donors to make grants to support new ideas that amplified the voices of citizens, and enabled governments to listen and respond. From the start, Making All Voices Count was also a learning programme. The objective of this learning was not only to bring about change during the programme’s life cycle, but also to leave a legacy that would help to ensure that future governance programmes and initiatives seeking to capitalise on the transformative potential of innovation and technology are more informed, inclusive and impactful. This programme learning report emerged from a wider process of analysing, discussing and synthesising the data and learning from the programme, which wove together evidence-based learning about technology for accountable governance initiatives with experiential learning on how best to support such work. The report highlights five of the lessons learned from Making All Voices Count about how – and how not – to run large, complex programmes that intend to support innovation in governance.